2018
DOI: 10.1002/adsc.201800119
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Procedure for the Synthesis of β‐Hydroxyallenamides via Homoallenylation of Aldehydes

Abstract: A simple one-pot synthesis of β-hydroxyallenamides is reported. This procedure entails chemo- and regioselective hydroboration of 3-en-1-ynyl-sulfonylamides with CyBH followed by homoallenylation of aldehydes to yield β-hydroxyallenamides (up to 94% yield and >20:1 dr). Controlled synthesis of up to three continuous stereochemical elements was realized. Density functional theory (DFT) calculations suggest a concerted Zimmerman-Traxler chair-like transition state. Initial results suggest that enantio- and diast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…Recently, chemo-and regioselective hydroboration of the triple bond in 3-en-1-ynyl-sulfonylamides (12) was achieved with Cy 2 BH to produce 2-dicylcohexylboryl-dienyl amides (12 a) in excellent yields. [21] Further homoallenylation of aldehydes gave β-hydroxyallenamides (12 c) with excellent diastereoselectivity (up to > 20:1 dr; Scheme 7). Density functional theory (DFT) calculation suggested that the origin of the diastereoselectivity was due to the transfer of homoallenyl group via Zimmerman-Traxler transition state (12 b, chair-like conformation).…”
Section: Catalyst Free Hydroboration Of Enynesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, chemo-and regioselective hydroboration of the triple bond in 3-en-1-ynyl-sulfonylamides (12) was achieved with Cy 2 BH to produce 2-dicylcohexylboryl-dienyl amides (12 a) in excellent yields. [21] Further homoallenylation of aldehydes gave β-hydroxyallenamides (12 c) with excellent diastereoselectivity (up to > 20:1 dr; Scheme 7). Density functional theory (DFT) calculation suggested that the origin of the diastereoselectivity was due to the transfer of homoallenyl group via Zimmerman-Traxler transition state (12 b, chair-like conformation).…”
Section: Catalyst Free Hydroboration Of Enynesmentioning
confidence: 99%
“…Recently, chemo‐ and regioselective hydroboration of the triple bond in 3‐en‐1‐ynyl‐sulfonylamides ( 12 ) was achieved with Cy 2 BH to produce 2‐dicylcohexylboryl‐dienyl amides ( 12 a ) in excellent yields . Further homoallenylation of aldehydes gave β ‐hydroxyallenamides ( 12 c ) with excellent diastereoselectivity (up to >20:1 dr; Scheme ).…”
Section: Catalyst Free Hydroboration Of Enynesmentioning
confidence: 99%
See 1 more Smart Citation